Combined impact of residual inflammatory risk and chronic kidney disease on long-term clinical outcomes in patients undergoing percutaneous coronary intervention. Issue 4 (April 2022) - Nishio, Ryota; Dohi, Tomotaka; Takeuchi, Mitsuhiro; Takahashi, Norihito; Endo, Hirohisa; Doi, Shinichiro; Okai, Iwao; Iwata, Hiroshi; Okazaki, Shinya; Miyauchi, Katsumi; Daida, Hiroyuki; Minamino, Tohru
Highlights: High residual inflammatory risk (RIR) is associated with cardiovascular disease risk Chronic kidney disease (CKD) increases the incidence of cardiovascular events RIR and CKD have an adverse effect on clinical outcomes Abstract: Background: Inflammatory status is associated with cardiovascular events in patients with coronary artery disease (CAD) and renal function impairment. Chronic kidney disease (CKD) increases the incidence of cardiovascular events. However, whether the presence of residual inflammatory risk (RIR) and CKD together has a synergistic effect on the long-term clinical outcomes of patients with stable CAD undergoing percutaneous coronary intervention (PCI) remains unclear. Methods: We assessed 2, 948 consecutive patients with stable CAD who underwent the first PCI from 2000 to 2016. Of these, we analyzed the data of patients (2, 087) with measurements of high-sensitivity C-reactive protein (hs-CRP) available at follow-up (6–9 months later). High RIR was defined as hs-CRP of >0.6 mg/L according to the median value at follow-up. Patients were classified into four groups: Group 1 (low RIR, non-CKD), Group 2 (high RIR, non-CKD), Group 3 (low RIR, CKD), and Group 4 (high RIR, CKD). We evaluated all-cause mortality and major adverse cardiac events (MACE). The median follow-up period was 5.2 (interquartile range, 1.9–9.9) years. Results: In total, 189 (16.1%) and 128 (11.2%) cases of all-cause mortality and MACE, respectively, were identified during follow-up. The rates of all-cause mortality and MACE were significantly higher in Group 4 than those in the other groups ( p <0.001). There was a stepwise increase in the incidence of all-cause mortality and MACE. Upon adjustment for important covariates, the presence of high RIR and/or CKD showed an independent association with a high incidence of MACE and all-cause mortality. Conclusions: The presence of high RIR and CKD conferred a synergistic adverse effect on the long-term clinical outcomes of patients undergoing PCI. Graphical Abstract: Graphical Abstract. Image, graphical abstract .